The Effect Of Green Accounting, Corporate Social Responsibility, And Good Corporate Governance On Firm Value - Amanta, Wafiqah Sakhi; Puspita, Ayu Fury (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This study aims to examine the effects of green accounting, corporate social responsibility, and good corporate governance, as reflected in managerial ownership, institutional ownership, and audit committees, on firm value. Variable firm value using the price-to-book-value ratio. This study is a quantitative study using secondary data obtained from the company's financial and sustainability reports. The study sample was determined using purposive non-probability sampling, comprising 14 companies listed on the SRI KEHATI Index of the Indonesia Stock Exchange during the period 2020 to 2024 that had accessible and complete data for all variables. Data analysis was conducted using multiple linear regression in SPSS version 26. The results indicate that green accounting, along with good corporate governance as reflected in managerial and institutional ownership, has a significant influence on firm value. In contrast, corporate social responsibility and good corporate governance, as reflected through the audit committee, do not have a substantial impact on firm value.